2021
DOI: 10.3390/biology10111130
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of RNA Modification Gene PUS7 as a Potential Biomarker of Ovarian Cancer

Abstract: RNA modifications are reversible, dynamically regulated, and involved in a variety of diseases such as cancers. Given the lack of efficient and reliable biomarkers for early diagnosis of ovarian cancer (OV), this study was designed to explore the role of RNA modification genes (RMGs) in the diagnosis of OV. Herein, 132 RMGs were retrieved in PubMed, 638 OV and 18 normal ovary samples were retrieved in The Cancer Genome Atlas (TCGA), and GSE18520 cohorts were collected for differential analysis. Finally, PUS7 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 42 publications
1
15
0
Order By: Relevance
“…The application of PUS7 inhibitors inhibited tumorigenesis and prolonged the life span of tumor-bearing mice ( Cui et al, 2021 ). In ovarian cancer, both mRNA and protein expression of PUS7 were higher in cancer tissues than in normal tissues ( Li et al, 2021 ). All these emerging findings showed the potential of PUSs as cancer biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…The application of PUS7 inhibitors inhibited tumorigenesis and prolonged the life span of tumor-bearing mice ( Cui et al, 2021 ). In ovarian cancer, both mRNA and protein expression of PUS7 were higher in cancer tissues than in normal tissues ( Li et al, 2021 ). All these emerging findings showed the potential of PUSs as cancer biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…m 6 A methyltransferases and demethyltransferases were also involved in ovarian cancer progression through m 6 A-dependent or independent regulation 11,14 . A previous study identi ed pseudouridine synthase 7 (PUS7) that catalyzed RNA pseudouridine might be a potential biomarker of ovarian cancer, but its underlying mechanisms were not explored 51 . Our previous analysis of m 5 C modi cation genes in ovarian cancer showed that a signature constructed based on m 5 C modi cation genes could predict the poor prognosis of ovarian cancer 52 .…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of FTO significantly promoted viability and autophagy, but reduced apoptosis in OCs ( 30 ). A bioinformatics analysis suggested that PUS7 was a potential marker for diagnosis and target for OC treatment ( 84 ). TET3 blocked epithelial-mesenchymal transition induced by TGF-β1 through demethylating miR-30d precursor gene promoter to suppress OCs ( 85 ).…”
Section: Discussionmentioning
confidence: 99%